2022
DOI: 10.3389/fimmu.2022.842605
|View full text |Cite
|
Sign up to set email alerts
|

Non-Muscle Myosin II Is Essential for the Negative Regulation of B-Cell Receptor Signaling and B-Cell Activation

Abstract: Antigen (Ag)-triggered B-cell receptor (BCR) signaling initiates antibody responses. However, prolonged or uncontrolled BCR signaling is associated with the development of self-reactive B-cells and autoimmune diseases. We previously showed that actin-mediated B-cell contraction on Ag-presenting surfaces negatively regulates BCR signaling. Non-muscle myosin II (NMII), an actin motor, is involved in B-cell development and antibody responses by mediating B-cell migration, cytokinesis, and Ag extraction from Ag-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 67 publications
2
21
0
Order By: Relevance
“…As non-muscle myosin II (NMII) is required for B-cell contraction (Seeley-Fallen et al . 2022), we examined the relationship between the formation of inner F-actin foci and the recruitment and reorganization of NMII in the contact zone using TIRF imaging of B-cells from mice expressing a GFP-NMIIA transgene.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As non-muscle myosin II (NMII) is required for B-cell contraction (Seeley-Fallen et al . 2022), we examined the relationship between the formation of inner F-actin foci and the recruitment and reorganization of NMII in the contact zone using TIRF imaging of B-cells from mice expressing a GFP-NMIIA transgene.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that B-cell contraction after spreading on antigen-presenting surfaces promotes BCR signaling attenuation (Liu et al . 2013a; Seeley-Fallen et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations